Readiness Analysis of Politeknik STMI Jakarta Towards Implementation and Certification of ISO 21001:2018 - Laksmi Ambarwati; Emi Rusmiati; Siti Aisyah (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Higher education has great demands and responsibilities to ensure their student graduates as highly competent human resources. Thus, effective and efficient management is required for higher education’s business process. To ensure their quality in process and result, compliance with national regulations and standards related to higher education is a must, and quality conformity with international standards is also one of the efforts of higher education institutions to improve their quality and competitiveness. ISO 21001:2018 is one of the international standards and best practice management systems for educational organizations that are widely used by various higher education institutions in the world. Considering Politeknik STMI Jakarta’s vision for resulting competent human resources, and that it is not yet certified by ISO 21001: 2018, this study is conducted to know the extent of readiness of Politeknik STMI Jakarta  towards implementation and certification of ISO 21001:2018. The method used is the gap analysis method between conditions existing in Politeknik STMI Jakarta to ISO 21001:2018 standard. The results showed that the level of readiness of Politeknik STMI Jakarta is 88.85% which showed that the implementation of the clause requirements is mostly carried out but not consistently. The conclusion that can be drawn from the research is that Politeknik STMI Jakarta is ready to implement and carry out ISO 21001: 2018 certification.